2020
DOI: 10.22452/ijie.vol13no1.1
|View full text |Cite
|
Sign up to set email alerts
|

Trade Policy, Infrastructural Development and Agricultural Sector Value Added in Nigeria

Abstract: The collapse of the international price of crude oil in 2015 and its attendant negative consequences on government fiscal capacity and development efforts re-echoed the need for Nigerians to return to agriculture as the surest means of conserving foreign exchange and revamping productive capacity. Within this context, this paper investigates, using the Autoregressive Distributed Lag methodology, the impact of Nigeria's trade policy and infrastructural development on agricultural value added. Findings show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…Their study showed that agricultural productivity before and after trade liberalisation significantly differed, which indicated that trade openness negatively affects agricultural output in both the long and short run. The result was consistent with the findings of Effiom and Ebi (2021), who reported that the liberalisation policy restricts the long-term growth of the value-added produced by the agricultural sector. However, these findings negate the earlier studies of Felix et al (2013a, b) and Muhammad and Atte (2006), who reported that trade liberalisation promotes the economic growth in Nigeria with positive developmental support in its agricultural sector.…”
Section: Impacts Of Trade and Economic Policies On The Nigerian Agric...supporting
confidence: 92%
See 1 more Smart Citation
“…Their study showed that agricultural productivity before and after trade liberalisation significantly differed, which indicated that trade openness negatively affects agricultural output in both the long and short run. The result was consistent with the findings of Effiom and Ebi (2021), who reported that the liberalisation policy restricts the long-term growth of the value-added produced by the agricultural sector. However, these findings negate the earlier studies of Felix et al (2013a, b) and Muhammad and Atte (2006), who reported that trade liberalisation promotes the economic growth in Nigeria with positive developmental support in its agricultural sector.…”
Section: Impacts Of Trade and Economic Policies On The Nigerian Agric...supporting
confidence: 92%
“…However, these findings negate the earlier studies of Felix et al (2013a, b) and Muhammad and Atte (2006), who reported that trade liberalisation promotes the economic growth in Nigeria with positive developmental support in its agricultural sector. According to Effiom and Ebi (2021), key infrastructure elements (telecommunications, roads and electricity consumption) had a significant relationship with and positively affected the agricultural sector. However, Felix et al (2013a) discovered that exports had a negative association with economic growth.…”
Section: Impacts Of Trade and Economic Policies On The Nigerian Agric...mentioning
confidence: 99%
“…Sebri and Abid (2012) stated that trade openness influences the creation of AVA. Nonetheless, Effiom and Ebi (2020) findings demonstrate that trade openness is a deterrent for AVA. This is because trade openness was implemented when domestic production capacity was low.…”
Section: Literature Review and Hypothesismentioning
confidence: 88%